Analisa Komunikasi Word of Mouth Dalam Mendukung Pemanfaatan Media Digital Berbasis Kepuasan Pengunjung - Rudi Prasetyo Ardi; Shandra Widiyanti (Jurnal Visi Manajemen, 2025)
Word-of-Mouth (WOM) communication plays a vital role in shaping the perception of tourism destinations and significantly influences tourists' decision-making processes. This is particularly true for Generation Z, a demographic cohort characterized by their high digital literacy, constant connectivity, and strong preference for authentic and unique experiences. Generation Z travelers tend to rely heavily on WOM, both traditional and digital (e-WOM), when selecting travel destinations, as they value peer recommendations over conventional advertising. One of the destinations that has gained popularity among this generation is Pantai Indah Kapuk (PIK), a rapidly developing coastal area known for its vibrant atmosphere, modern attractions, and aesthetic appeal suitable for social media sharing.This study aims to examine the impact of WOM communication on the satisfaction and overall tourism experience of Generation Z visitors at PIK. The research adopts a quantitative approach using survey methods to collect data from Generation Z tourists who have visited PIK. Variables measured include the source and credibility of WOM, the influence of WOM on decision-making, perceived value, satisfaction, and the quality of the tourism experience.The findings are expected to provide insights into how WOM shapes tourist behavior, enhances destination satisfaction, and contributes to memorable tourism experiences among Generation Z. Furthermore, the study aims to offer recommendations for destination marketers and tourism stakeholders to effectively leverage WOM as a strategic tool in promoting destinations and engaging young travelers in meaningful ways.